Quantitative 23Na-MRI: From Pre-Clinical to Clinical Practice - Wetterling, Friedrich (My University, 2010)
Quantitative 23Na-MRI (qNa-MRI) is a non-invasive technique which allows for measuring subtle changes in the Tissue Sodium Concentration (TSC) after ischaemic stroke. Although, an increase in TSC after stroke has been reported many times in the literature [1-5] the underlying mechanisms related to the regionally TSC changes have only recently been investigated in an animal stroke model. The in vivo TSC time-course data revealed that the time point at which the TSC started to increase varied significantly in still viable (penumbra) and permanently damaged (core) tissue [6]. A threshold at normal TSC level could consequently serve to differentiate between penumbra and core tissue after stroke. However, the TSC has never been studied during the acute stroke phase in humans (<6h after Onset) due to the challenges involved in adding qNaMRI to the standard 1H-MRI protocol. The aim of this study was to develop a comprehensive stroke protocol for 1H and 23Na MRI of acute stroke patients at 3T.
41st annual meeting of the German Association for Medical Physics (DGMP)
PUBLISHED
Freiburg, Germany